All that wheezes is not asthma. (27th February 2014) - Koul, Parvaiz A; Khan, Umar H; Shah, Tajamul Hussain; Dar, Abdul Majid
Abstract : A young woman was admitted with respiratory failure. Prior to her admission, she had been treated for clinical bronchial asthma for about 2 years for recurrent wheezing. Endotracheal intubation was difficult. A fibroptic brochoscopy, while the patient was ventilated, revealed a central tracheal tumour compromising >90% of the tracheal lumen. The tumour was cored out during rigid bronchoscopy while ventilating the patient through tracheostomy. Histopathology of the tumour was suggestive of adenoid cystic carcinoma.